The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0058289
|View full text |Cite
|
Sign up to set email alerts
|

The Head Tracks and Gaze Predicts: How the World’s Best Batters Hit a Ball

Abstract: Hitters in fast ball-sports do not align their gaze with the ball throughout ball-flight; rather, they use predictive eye movement strategies that contribute towards their level of interceptive skill. Existing studies claim that (i) baseball and cricket batters cannot track the ball because it moves too quickly to be tracked by the eyes, and that consequently (ii) batters do not – and possibly cannot – watch the ball at the moment they hit it. However, to date no studies have examined the gaze of truly elite b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
187
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(202 citation statements)
references
References 35 publications
14
187
1
Order By: Relevance
“…If this is the case, an improvement in color perception should be observed in experts at the point of bat-ball contact; however, the present findings did not indicate such an improvement. In addition, Land and McLeod (2000) found that a saccade occurred after the pursuit eye movement during the early phase of ball flight (see also Croft et al, 2010;Mann, Spratford, & Abernethy, 2013). In the present study, the CR reduction in baseball players had already occurred by early-phase ball flight.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…If this is the case, an improvement in color perception should be observed in experts at the point of bat-ball contact; however, the present findings did not indicate such an improvement. In addition, Land and McLeod (2000) found that a saccade occurred after the pursuit eye movement during the early phase of ball flight (see also Croft et al, 2010;Mann, Spratford, & Abernethy, 2013). In the present study, the CR reduction in baseball players had already occurred by early-phase ball flight.…”
Section: Discussionsupporting
confidence: 63%
“…One alternative factor may have been the limitation inherent in the visual tracking of task stimuli. Previous studies in fast-ball sports have demonstrated that batters cannot track the ball flight path until bat-ball contact during the batting act (Bahill & LaRitz, 1984;Hubbard & Seng, 1954;Land & McLeod, 2000;Mann et al, 2013). Thus, the participants in the present study may have been less proficient at detecting color change during late-phase interception because they were unable to track the target until the end of ball flight.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…When asked to indicate where they thought they were looking when presented with a series of images showing the flight-path of the ball coming towards them, the same player reported that his gaze was always directed towards the ball and that he could not recollect any times at which his gaze was not aligned with the ball. Similarly in a recent examination of the gaze behaviour of some of the world's best cricket batters, Mann et al (2013) found that the batters tended to move their gaze ahead of the ball towards the point where they anticipated their bat would make contact with the ball. Effectively this ensured that the batters could 'watch the ball onto the bat' when they made contact with the ball.…”
Section: Conscious Awareness Of Gaze In the Control Of Visually-guidementioning
confidence: 90%
“…In the twenty first century, several other researchers have devised alternative sport "visual" techniques-Mac Leod [13], Lafont [14][15][16][17], Vickers [18], Albernethy [19] which re-confirm the eye physical limits and stress out the necessity to focus on a sound cognitive vision strategy rather than sight skills.…”
Section: Literature Reviewmentioning
confidence: 99%